Evolving Concepts in Cardiometabolic Risk: A Review of Recent Evidence - Omar Elsaka (Research in Cardiovascular Medicine)
Although traditional methods of assessing cardiometabolic risk have focused on a few factors, new research is showing the importance of a broader range of factors. These include chronic inflammation, gut microbiome composition, and sleep disturbances, among others. In addition, environmental factors and socioeconomic disparities play a role. By incorporating both conventional and emerging factors into personalized risk assessment, we can better understand and address the multifaceted nature of cardiometabolic risk. This approach will help improve individual and community health outcomes. The development of new diagnostic tools, risk calculators, and personalized treatment plans is an exciting step forward in our understanding of cardiometabolic risk. By embracing this expanded knowledge, we can work toward a healthier future for everyone.